Natural law in Judaism - Novak, David (Cambridge University Press, 1998)
This 1998 book presents a theory of natural law, significant for the study of Judaism, philosophy and comparative ethics. It demonstrates that the assumption that Judaism has no natural law theory to speak of is simply wrong. The book shows how natural law theory, using a variety of different terms for itself throughout the ages, has been a constant element in Jewish thought. The book sorts out the varieties of Jewish natural law theory, illuminating their strengths and weaknesses. It also presents a case for utilizing natural law theory in order to deal with theological and philosophical questions in Judaism's ongoing reflection on its own meaning and its meaning for the wider world. David Novak combines great erudition in the Jewish tradition, the history of philosophy and law, and the imagination to argue for Judaism in the context of current debates, both theoretical and practical.